BIOGAS PRODUCTION AND ENGINE CONVERSION FROM DIESEL ENGINE TO BIOGAS ENGINE FOR LIGHTING IN RURAL AREA - Tun, Seint Thandar (185P -3466)
The research of alternative fuels implemented in internal combustion engines are becoming the subjects of interest nowadays. This paper describes a production of biogas from cow dung, diesel engine conversion process with piston modification of ZH1115 diesel engine. To produce biogas, the usual practice is to mix water with some organic material, such as cow dung (a free source of the appropriate micro-organisms). The slurry is placed in a leak-proof container (called a digester) and leaves it to ferment. After several days at suitable temperature, sufficient methane will have formed to make a combustible gas. Fix dome type of biogas plant is chosen in this gas production for cost saving and to produce sufficient gas at lower temperature. The biogas engine which are modified from diesel engine emphases the ignition system, gas governing and carburetion systems along with a change in compression ratio, in some cases also a change in the combustion chamber. Since diesel engine cannot be operated by biogas alone, this paper covers the conversion of diesel to spark ignition engine i.e. conversion of four stroke of ZH1115 diesel engine to biogas engine based on 30 biogas inlet holes which was recommended by the experienced designers. This paper also describes methods of reducing compression ratio, changing ignition system with timing and fueling system, the comparisons of technical parameters and performance between ZH1115 diesel engine and converted biogas engine. It describes the criteria of technological selections, engineering aspects and short term and long term plans for lighting. The goal to develop and implement BIOGAS engine and use biogas as the renewable energy and bio-fertilizer is to control pollution, to protect environment, to develop rural area and also to reach the ambitious emissions goals and to reduce dependence on imported foreign oil.